Do Implicit Theories About Ability Predict Self-Reports and Behavior-Proximal Measures of Primary School Students’ In-Class Cognitive and Metacognitive Learning Strategy Use? - Matthes, Benjamin; Stoeger, Heidrun (Frontiers in Psychology, 2021)
Although studies show relations between implicit theories about ability (ITs) and cognitive as well as metacognitive learning strategy use, existing studies suffer from an overreliance on broad-brush self-report measures of strategy use and limited ecological validity. Moreover, studies rarely examine younger students, and research on ITs and how much students benefit from interventions on learning strategies is lacking. Therefore, we investigated in ecologically valid settings (regular classroom instruction) whether primary school students’ ITs are related to their use of cognitive strategies (text reduction strategies based on identifying a text’s main ideas) and metacognitive strategies, assessed with (a) typical self-report scales and (b) more behavior-proximal measures. We also investigated whether students’ ITs predict how much they benefit from a previously evaluated four-week intervention on cognitive and metacognitive strategies during regular classroom instruction (i.e., how much self-report scales and behavior-proximal measures for strategy use increase over the course of the intervention). Participants were 436 German primary school students (third and fourth graders). The data were analyzed using mixed linear regression analyses. Strength of students’ incremental theory was positively related to metacognitive strategy use, but not cognitive strategy use, when measured with self-report scales. For behavior-proximal measures, strength of incremental theory was positively related to the effectiveness of students’ cognitive strategy use and their extent of strategy monitoring (one of the two metacognitive strategies examined), but not to the quality of their goal setting (the second metacognitive strategy). Unexpectedly, students with a stronger incremental theory did not benefit more from the intervention.